How to overcome the short-term costs of the climate transition? The benefits of the green transition - Lorenzo Forni; Massimo Tavoni (EconPol Forum, 2023)
Transitioning to a climate-resilient future can offer significant economic benefits when compared to maintaining current emissions levels. Renewables and electrification promise reducing dependence on fossil fuels, benefiting both the environment and human well-being. The transition to a green economy, however, faces shortterm challenges, including stranded assets and skill obsolescence. Overcoming these obstacles requires securing public buy-in, addressing the disparity between private costs and societal benefits, and developing comprehensive policy strategie.s Public acceptance of climate policies hinges on perceived fairness and policy efficacy, with effective communication about benefits playing a pivotal role. While carbon revenue recycling can gain short-term public support, a holistic approach, integrating various mitigation strategies and transparent communication, is vital for a sustainable transition. Several authors emphasize the importance of aggressive early action for a successful green transition, highlighting the momentum and cost reductions achieved with the diffusion of green goods and technologies. Challenges such as political divides, economic disparities, and the interplay between market and government failures can potentially hinder the positive feedback loop and derail green transition efforts. To ensure success, a concerted effort from both the public and private sectors, backed by rigorous research to understand societal behaviors and attitudes, is necessary.
Keywords: 330